2013
DOI: 10.1159/000354387
|View full text |Cite
|
Sign up to set email alerts
|

Annular Elastolytic Giant Cell Granuloma Associated to Late-Onset X-Linked Dominant Protoporphyria

Abstract: X-linked dominant protoporphyria (XLDPP) is a genetic disorder that affects the synthesis of the heme group due to an increase in delta-aminolaevulinate synthase 2 (ALAS2) enzyme activity. Moreover, annular elastolytic giant-cell granuloma (AEGCG) is a rare reactive granulomatous dermatosis, usually associated with actinic damage. An 86-year-old man presented with edematous-erythematous lesions in photoexposed areas of the face and on the dorsum of both hands. Protoporphyrin levels in serum and feces were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Previous reports describing GCEG lesions not being found in areas devoid of elastic fibers, such as in burn scar or striae distensae, indicate that elastic fiber is involved in pathogenesis. GCEG has been reported to be associated with several systemic diseases, such as diabetes mellitus, alcoholic liver disease, temporal arteritis, cutaneous amyloidosis, and protoporphyria . It has been proposed that unstable metabolic status and vasculopathy may lead to structural damage of elastic fibers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports describing GCEG lesions not being found in areas devoid of elastic fibers, such as in burn scar or striae distensae, indicate that elastic fiber is involved in pathogenesis. GCEG has been reported to be associated with several systemic diseases, such as diabetes mellitus, alcoholic liver disease, temporal arteritis, cutaneous amyloidosis, and protoporphyria . It has been proposed that unstable metabolic status and vasculopathy may lead to structural damage of elastic fibers .…”
Section: Discussionmentioning
confidence: 99%
“…Most of our patients received topical steroid therapy only. Numerous therapies, including topical steroid, topical pimecrolimus, excision, cryotherapy, ultraviolet A therapy with psoralen, systemic clofazimine, oral chloroquine/hydroxychloroquine, systemic corticosteroids, systemic cyclosporine, fumaric acid, dapsone, tranilast, and isotretinoin, have been reported, but the therapeutic responses vary in these reports. Our series showed that approximately one‐third of the patients exhibited complete resolution, but many of them presented lesions that waxed and waned.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, reports associating lesions of AG in skin affected by late-onset X-linked protoporphyria[ 7 ] and vitiligo[ 8 ] again corroborate the causative role of elastotic fibers and solar damage.…”
Section: Discussionmentioning
confidence: 82%
“…We believe this cytokine profile of adipose tissue may have favoured a granulomatous type reaction against the nearby glycated elastic fibres. Nevertheless, other related disorders have been reported, specifically sarcoidosis, temporal arteritis, erythropoietic protoporphyria, and haematological and solid malignancies 1 3 8–11. Therefore, atypical cases of EGCG, particularly those non-photodistributed, demand the assessment of other comorbidities.…”
Section: Discussionmentioning
confidence: 99%